Carbon dioxide-assisted Torrefaction of Maize Cobs by Thermogravimetry: Product Yield and Energy Recovery Potentials - Nyakuma, Bemgba B.; M. Ajibade, Samuel-Soma; Adebayo, Victor B.; Alkali, Habib; Otitolaiye, Victor O.; Audu, Jemilatu O.; Bashir, Faizah M.; Dodo, Yakubu A.; Mahmoud, Abubakar S.; Oladokun, Olagoke (Physics and Chemistry of Solid State, 2022)
The objective of this study is to examine the potential product yields and energy recovery of maize cobs (MC) through carbon dioxide-assisted torrefaction using thermogravimetric analysis (TGA). The CO2-assisted torrefaction of MC was performed from 240 °C to 300 °C (Δ 30 °C) for the residence time of 30 minutes based on the selected non-isothermal/isothermal heating program of the TGA. Furthermore, the physicochemical, microstructure and mineral characteristics of MC were examined. The results showed that the CO2-torrefaction of MC resulted in a mass loss (ML) ranging from 18.45% to 55.17%, which resulted in the mass yield (MY) ranging from 81.55% to 44.83%. The HHV of the solid product was in the range from 22.55 MJ/kg to 26 MJ/kg, which indicates the CO2-torrefaction process enhanced the energy content of MC by 40% – 60%. In conclusion, the findings showed that the CO2 torrefaction is a practical, sustainable, and cost-effective approach for the valorization of MC into a clean solid biofuel for enhanced energy recovery.